Contextual Simulations for Information Retrieval Evaluation - White, Ryen W. (Information Retrieval in Context Workshop (IRiX 2005, part of SGIR 2005), Salvador, Brazil, 2003)
Non-interactive evaluations of Information Retrieval (IR) systems do not model many of the contextual factors that influence real users' information seeking. As such, they may give overly-simplified grounds for IR system comparison. This paper advocates the use of rich contextual simulations (i.e., simulations of user behavior and the factors that influence it) to extend and enhance the non-interactive evaluation of IR systems and the iterative development of interfaces that use their algorithms.